2019
DOI: 10.3892/or.2019.7006
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Opa interacting protein�5 increases the progression of liver cancer via BMPR2/JUN/CHEK1/RAC1 dysregulation

Abstract: Opa interacting protein 5 (OIP5) overexpression is associated with human carcinoma. However, its biological function, underlying mechanism and clinical significance in liver cancer remain unknown. In the present study, the effects of OIP5 expression on liver cancer, and the mechanisms regulating these effects, were investigated. OIP5 expression was measured in human hepatocellular carcinoma (HCC) tissues and liver cancer cell lines. The effect of OIP5 knockdown on tumorigenesis was also detected in nude mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
(65 reference statements)
2
15
0
Order By: Relevance
“…OIP5 was found to be highly expressed in many types of cancer. Studies have confirmed its role in the progression of hepatocellular, bladder, and gastric cancers 35–37 . Interestingly, OIP5 was also recognized as a downstream gene of E2F1 in the tumorigenesis and metastasis of glioblastoma, 38 which is consistent with the GSEA enrichment to E2F target in our study (Figure S3A,B).…”
Section: Discussionsupporting
confidence: 89%
“…OIP5 was found to be highly expressed in many types of cancer. Studies have confirmed its role in the progression of hepatocellular, bladder, and gastric cancers 35–37 . Interestingly, OIP5 was also recognized as a downstream gene of E2F1 in the tumorigenesis and metastasis of glioblastoma, 38 which is consistent with the GSEA enrichment to E2F target in our study (Figure S3A,B).…”
Section: Discussionsupporting
confidence: 89%
“…It can induce melanocytes to transform into mesenchymal-like cells, inhibit apoptosis, and enhance tumorigenesis (81). OPA interacting protein-5 (OIP5) regulates proliferation, apoptosis and cell cycle of HCC cells by influencing BMPR2-JUN-CHEK1-Rac1 signal axis (82).…”
Section: Rac1 Participates In the Cell Cycle Apoptosis And Proliferationmentioning
confidence: 99%
“… 13 Using siRNA-mediated knockdown studies, we found that OIP5 silencing significantly inhibits glioma cell survival. Previous studies have shown that the JAK2/STAT3 pathway in nasopharyngeal carcinoma, 18 BMPR2/JUN/CHEK1/RAC1 in liver cancer, 19 miR-139-5p/NOTCH1 in breast cancer, 12 and mTORC2 and p38/PTEN in hepatocellular carcinoma, 20 and E2F1 signaling in glioblastoma 21 are involved in OIP5-regulated tumor progression. These pathways are primarily associated with tumor cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 98%